PENERAPAN STRATEGI MARKETING 4.0 PADA WISATA MUSEUM SEPULUH NOVEMBER (TUGU PAHLAWAN) SURABAYA - Tresyanto, Citra Anggraini; Ayu, Stephanie Astrid (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.09.NO.04.TAHUN 2020DO - 10.24843/EEB.2020.v09.i04.p03, 2020)
The Ten November Museum which depicts the struggle of the Suroboyo arek during the struggle era, this is the reason why the number of community visits to the November 10 Museum is very small. With the sophistication of technology, this should not be an obstacle to keep on informing the existence of the November 10 Museum, even more so among today's youth, whose world is very close to the development of Information Technology. The purpose of this research is to be more aggressive in introducing the existence of the Tugu Pahlawan museum by applying Marketing Strategy 4.0 which focuses on the application of 5A (Aware, Appeal, Ask, Act, Advocate). This study uses a qualitative approach with descriptive analytic methods. Data collection techniques in this research are field studies and literature studies. The primary data of this study were from observations and interviews with the public and museum officials as well as other informants needed to obtain a more complete picture, while the secondary data of this study were processed data from museum officials. The results of this study improve visiting the need for information on the existence of the museum, provide an interesting program, officers must be able to answer questions well and easily understood by visitors, the public is given appropriate information and promote the museum through social media.